Analysis of Natural Semantic Metalanguage in “History” Song Lyrics (Conference on English Language Teaching, 2023)
Natural semantic metalanguage (NSM) was developed to reveal meaning, both agreement and difference. Because the paraphrase meaning is expressed in a metalanguage that derives from real language, NSM theory has two advantages: first, it may be accepted by all speakers; second, NSM is constantly open to adjusting and modifying its representation of meaning. The original meaning, which has a universal lexicon, is a key NSM premise. To achieve this goal, NSM seeks universal meaning. This article analyzed the words in the lyrics of the song "history" by One Direction. This study aims to analysed song lyrics using the natural semantic metalanguage (NSM) approach developed by Anna Wierzbicka. Through cross-language semantic research, Wierzbicka has devoted many years to creating the NSM hypothesis. This analysis is related to semantic primes, allolexy and polysemy. The data from this study are the lyrics of One Direction's song entitled History. The writer analyzes the data from the lyrics of the song. After finding the lyrics of the song, the data analyzes it based on the natural semantic metalanguage approach related to semantic prime, allolexy, and polysemy. The results show that the lyric contains semantic prime, allolexy and polysemy components.